Faktor-Faktor yang Mempengaruhi Financial Distress (Studi Kasus Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2017–2021) - Candra Irawan (CV Edujavare Publishing, 2024)
This study aims to empirically examine the influence of Profitability and Leverage on financial distress in food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. Eighteen companies were sampled for this research. The data analysis results indicate that Profitability, measured by Return On Assets (ROA), has a positive and significant partial effect on financial distress. Conversely, Leverage, measured by Debt to Asset Ratio (DAR), has a negative and significant partial effect on financial distress. Furthermore, simultaneously, both variables together have a significant impact on financial distress in food and beverage companies listed on the IDX during the study period. These findings contribute to understanding the factors influencing financial distress levels in the industry. The practical and theoretical implications of this research are relevant for managerial decision-making and financial strategy development. This abstract succinctly summarizes the key research findings, highlighting their practical and theoretical contributions.